Outcome for patients colonised with Burkholderia cepacia in a Birmingham adult cystic fibrosis clinic and the end of an epidemic. Issue 4 (April 1996) - Muhdi, K; Edenborough, F P; Gumery, L; O'Hickey, S; Smith, E G; Smith, D L; Stableforth, D E
Abstract : BACKGROUND: There has been increasing concern since 1979 about the emergence of Pseudomonas cepacia (Burkholderia cepacia) in patients with cystic fibrosis in the UK and elsewhere. Colonisation of the sputum has been shown to be associated with increased morbidity and mortality. Evidence suggests person to person transmission and some centres have segregated those colonised with B cepacia from other patients with cystic fibrosis. The outcome of patients colonised by B cepacia has been studied, together with the effects of strict segregation. METHODS: The outcome in 18 patients with sputum colonised by B cepacia was compared with that in age, sex, and severity matched controls with no evidence of B cepacia colonisation by a retrospective case note study. RESULTS: No difference between cases or controls were found in the 24 month period prior to colonisation by B cepacia in lung function, number of days in hospital, or outpatient visits. Colonisation led to an increased rate of loss of lung function and utilisation of hospital services. There was an increase in the numbers of transplants and deaths amongst the cases. Since 1992 there have been only three new cases of B cepacia colonisation and the incidence and prevalence of the organism has fallen dramatically since segregation commenced. CONCLUSIONS: B cepacia appears to be linked to the decline in colonised individuals. There was no evidence that colonisation occurred in patients declining for other reasons. B cepacia colonisation confers a worse prognosis than Pseudomonas aeruginosa alone. Segregation appears to limit the spread of the organism from infected individuals to other patients with cystic fibrosis.